2020
DOI: 10.1007/s40266-020-00753-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Naldemedine for the Treatment of Opioid-Induced Constipation in Patients with Chronic Non-Cancer Pain Receiving Opioid Therapy: A Subgroup Analysis of Patients ≥ 65 Years of Age

Abstract: Background Opioid-induced constipation (OIC), the most common side effect of opioid treatment, is under-recognized and undertreated in older patients. Naldemedine, an oral, peripherally acting μ-opioid receptor antagonist (PAMORA), is approved in Japan, the United States, and the European Union for treatment of OIC in adult patients. Objective This integrated analysis of three phase 3 trials (COMPOSE-1, COMPOSE-2, and COMPOSE-3) evaluated the safety and efficacy of naldemedine for up to 12 weeks in a subgroup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Due to the high clinical relevance of ORs agonists in pain management, our study was limited to the assessment of the action of agonists, not antagonists, in the GI tract. In clinics, the only antagonists that are applied in patients are peripherally acting antagonists of MOP receptors, such as methylnaltrexone [ 31 ] or naldemedine [ 32 ]. Noteworthy, it was reported that their activity in the human GI tract was independent of age [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high clinical relevance of ORs agonists in pain management, our study was limited to the assessment of the action of agonists, not antagonists, in the GI tract. In clinics, the only antagonists that are applied in patients are peripherally acting antagonists of MOP receptors, such as methylnaltrexone [ 31 ] or naldemedine [ 32 ]. Noteworthy, it was reported that their activity in the human GI tract was independent of age [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinics, the only antagonists that are applied in patients are peripherally acting antagonists of MOP receptors, such as methylnaltrexone [ 31 ] or naldemedine [ 32 ]. Noteworthy, it was reported that their activity in the human GI tract was independent of age [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although elderly patients may generally be excluded from clinical trials, COMPOSE-4 and -5 included patients over 20 years of age, with no upper age limit [6]. In a subgroup analysis of phase III trials, naldemedine had been reported to be generally well tolerated and effective in patients over 65 years of age suffering from chronic non-cancer pain [13]. This analysis appears to suggest that naldemedine can be effectively and safely used to treat older populations.…”
Section: Discussionmentioning
confidence: 99%
“…Safety: Naldemedine was generally well tolerated in terms of potential adverse effects. One study evaluated the safety and efficacy of naldemedine for up to 12 weeks in a subgroup of patients aged over 65 years from three trials (COMPOSE-1, COMPOSE-2 and COMPOSE-3) [50]. In these studies, the incidence of TEAEs in the naldemedine group (45.9%) was comparable to that in patients receiving placebo (51.6%).…”
Section: Bowel Movements Authormentioning
confidence: 99%